2021
DOI: 10.1177/07311214211040933
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue Editors’ Introduction: A Sociology of Firearms for the Twenty-First Century

Abstract: This special issue of Sociological Perspectives arrives amid a renaissance in the academic study of guns in recent years. In addition to individual books and articles, this collection sits alongside several other recent edited volumes (Carlson, Goss, and Shapira 2019; Fisher and Hovey 2021; Obert, Poe, and Sarat 2019) and special issues of journals (Metzl as editor for Palgrave Communications in 2019 and Dowd-Arrow, Burdette, and Hill as editors for Sociological Inquiry in 2021). These works contribute new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As Yamane (2017) has noted, sociological perspectives on guns have been surprisingly underdeveloped. Although recent special issues on "guns and society" have attempted to broaden this area of study (Dowd-Arrow, Hill, and Burdette 2020;Steidley and Yamane 2022), scholars have mostly focused on a narrow range of research topics, including patterns and correlates of gun ownership (Dowd-Arrow, Hill, and Burdette 2019;Legault 2008), the changing cultural meanings associated with owning and using firearms in the United States (Carlson 2015b;Mencken and Froese 2019), and the relationship between gun ownership and well-being (Dowd-Arrow et al 2019;Hill et al 2020aHill et al , 2020bHill et al , 2022. Studies of religiosity and gun-related outcomes have been identified as especially "rudimentary" (Ellison et al 2021).…”
mentioning
confidence: 99%
“…As Yamane (2017) has noted, sociological perspectives on guns have been surprisingly underdeveloped. Although recent special issues on "guns and society" have attempted to broaden this area of study (Dowd-Arrow, Hill, and Burdette 2020;Steidley and Yamane 2022), scholars have mostly focused on a narrow range of research topics, including patterns and correlates of gun ownership (Dowd-Arrow, Hill, and Burdette 2019;Legault 2008), the changing cultural meanings associated with owning and using firearms in the United States (Carlson 2015b;Mencken and Froese 2019), and the relationship between gun ownership and well-being (Dowd-Arrow et al 2019;Hill et al 2020aHill et al , 2020bHill et al , 2022. Studies of religiosity and gun-related outcomes have been identified as especially "rudimentary" (Ellison et al 2021).…”
mentioning
confidence: 99%